ʻAnusō̜n ngān phrarātchathān phlœ̄ng sop Nāi Sakun Thamangraksat Bō̜.Mō̜., Čhō̜.Mō̜. na chāpanasathān Wat Thāt Thō̜ng, Wansao thī 16 Mīnākhom Phutthasakkarāt 2556. - Sakun Thamangraksat, 1923-2012. ([Krung Thēp : Khrō̜pkhrūa Thamangraksat], 2013)
Cremation volume for Sakun Thamangraksat, 1923-2012; comprises condolences, biography and article on energy conservation.
Keywords: Sakun Thamangraksat, -- 1923-2012 -- Death and burial; Engineers -- Thailand -- Biography; Energy conservation -- Thailand